If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2c + -3d)(7c + 4d) = 0 Multiply (2c + -3d) * (7c + 4d) (2c * (7c + 4d) + -3d * (7c + 4d)) = 0 ((7c * 2c + 4d * 2c) + -3d * (7c + 4d)) = 0 Reorder the terms: ((8cd + 14c2) + -3d * (7c + 4d)) = 0 ((8cd + 14c2) + -3d * (7c + 4d)) = 0 (8cd + 14c2 + (7c * -3d + 4d * -3d)) = 0 (8cd + 14c2 + (-21cd + -12d2)) = 0 Reorder the terms: (8cd + -21cd + 14c2 + -12d2) = 0 Combine like terms: 8cd + -21cd = -13cd (-13cd + 14c2 + -12d2) = 0 Solving -13cd + 14c2 + -12d2 = 0 Solving for variable 'c'. Factor a trinomial. (2c + -3d)(7c + 4d) = 0Subproblem 1
Set the factor '(2c + -3d)' equal to zero and attempt to solve: Simplifying 2c + -3d = 0 Solving 2c + -3d = 0 Move all terms containing c to the left, all other terms to the right. Add '3d' to each side of the equation. 2c + -3d + 3d = 0 + 3d Combine like terms: -3d + 3d = 0 2c + 0 = 0 + 3d 2c = 0 + 3d Remove the zero: 2c = 3d Divide each side by '2'. c = 1.5d Simplifying c = 1.5dSubproblem 2
Set the factor '(7c + 4d)' equal to zero and attempt to solve: Simplifying 7c + 4d = 0 Solving 7c + 4d = 0 Move all terms containing c to the left, all other terms to the right. Add '-4d' to each side of the equation. 7c + 4d + -4d = 0 + -4d Combine like terms: 4d + -4d = 0 7c + 0 = 0 + -4d 7c = 0 + -4d Remove the zero: 7c = -4d Divide each side by '7'. c = -0.5714285714d Simplifying c = -0.5714285714dSolution
c = {1.5d, -0.5714285714d}
| 8+[9x-(7-7x)]= | | 7x-36+3x= | | f(8)=24 | | 8+[2x-(7-9x)]= | | f(6)=24 | | 17x+47+37x-33= | | 15/27/3*2= | | f(7)=24 | | 3x+4+5x-12= | | X-1/2y=6z | | 3p+7p-8p-4p= | | 8a+b-4a+11b= | | 4.6(2.5x-2)=6.9 | | 44/(-4/3)= | | T=2x^2 | | A-5b=c | | 2(1.5x+4)=x-0.8 | | g(x)=-x^2-10x-3 | | 0.27(12)*0.03x=2.16+0.09x | | 5x-30+4x=180 | | 1.5(5-2h)=2.0h | | X+4x+5x-30=180 | | -13x=9 | | F(x)=x^4+7x+1 | | x/6=x/7-13 | | 2(x-4)+8=4 | | 7(r+7)=5r+5a | | 2x-7=3x-4 | | F(x)=e^2x-13 | | 17-20y=-3 | | 4x-10+2x+7+7x-25=180 | | 5x-7=8+4x |